Granulosa Cell Tumour Early: Differences With Juvenile And Adult Cases. Literature Review. Comment. - Pereda-Garay, José (2016)
Clinical picture and karyotype of perinatal cases of Granulosa Cell tumor are reviewed comparing them with cases of other age groups described in the literatura. A group of Granulosa Cell Tumor in the testis of newborns presents clinical differences, as in their karyotype, and should be considered with merits to be studied.